2022
DOI: 10.1587/transcom.2021mep0001
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral-Based Model for Describing Social Polarization in Online Communities

Abstract: The phenomenon known as social polarization, in which a social group splits into two or more groups, can cause division of the society by causing the radicalization of opinions and the spread of misinformation, is particularly significant in online communities. To develop technologies to mitigate the effects of polarization in online social networks, it is necessary to understand the mechanism driving its occurrence. There are some models of social polarization in which network structure and users' opinions ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results in [123] suggest that this may be the case as they showed that most individuals from a network over time switch to opposite sentiments about the preconceived belief. The results obtained in [111] suggest that another possible way to revert polarization is to shield the members from their corresponding echo chambers, allowing them to access the ideas of members outside these chambers freely.…”
Section: Polarization Dimension As Shown In Tablementioning
confidence: 97%
“…The results in [123] suggest that this may be the case as they showed that most individuals from a network over time switch to opposite sentiments about the preconceived belief. The results obtained in [111] suggest that another possible way to revert polarization is to shield the members from their corresponding echo chambers, allowing them to access the ideas of members outside these chambers freely.…”
Section: Polarization Dimension As Shown In Tablementioning
confidence: 97%